Mechanisms Maintaining Additive Genetic Variance in Fitness in Red Squirrels - McFarlane, Samantha Eryn (University of Guelph, 2012)
A trait must genetically correlate with fitness in order to evolve, however, theory suggests that strong directional selection should erode additive genetic variance (Va) in fitness and limit future evolutionary potential. Sexual antagonism and temporal fluctuations in selection are mechanisms that could maintain Va in fitness. Maternal genetic effects could be an additional source of adaptive genetic variation. I used ‘animal models’ to examine a long-term population of red squirrels to determine 1) if either sexual antagonism or temporal fluctuations in selection were maintaining direct Va in fitness or 2) if maternal genetic effects were a source of indirect Va in fitness. While there were environmental trade-offs on juvenile survival, neither sexual antagonism nor temporal fluctuations in selection maintained Va in fitness. Maternal genetic effects on fitness were significant and provide the Va in fitness needed for rapid microevolution. This is the first instance of maternal genetic effects demonstrated as the only genetic variance available for microevolution. Northern Scientific Training Program Arctic Institute of North America American Society of Mammologists, Queen Elizabeth II Graduate Scholarship in Science and Technology Natural Sciences and Engineering Research Council of Canada Discovery (to Andrew McAdam) NSF (to Andrew McAdam)